Dhvar5- and MSI78-coated titanium are bactericidal against methicillin-resistant Staphylococcus aureus, immunomodulatory and osteogenic - Costa, B.; Coelho, J.; Silva, V.; Shahrour, H.; Costa, N. A. [UNESP]; Ribeiro, A. R.; Santos, S. G.; Costa, F.; Martínez-de-Tejada, G.; Monteiro, C.; Martins, M. C.L. (Elsevier, 2025)
Infection is one of the major issues associated with the failure of orthopedic devices, mainly due to implant bacterial colonization, biofilm formation, and associated antibiotic resistance. Antimicrobial peptides (AMP) are a promising alternative to conventional antibiotics given their broad-spectrum of activity, low propensity to induce bacterial resistance, and ability to modulate host immune responses. Dhvar5 (LLLFLLKKRKKRKY) and MSI78 (GIGKFLKKAKKFGKAFVKILKK) are two AMP with broad-spectrum activity against bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), one of the most problematic etiologic agents in Orthopedic Devices-Related Infections (ODRI). This work aims to evaluate the bactericidal, immunomodulatory and osteogenic potential of Dhvar5- and MSI78-coated titanium surfaces (AMP-Ti). Two AMP-Ti surfaces were successfully obtained by grafting Dhvar5 (0.8 ± 0.1 µM/mm2) or MSI78 (0.5 ± 0.3 µM/mm2) onto titanium substrates through a polydopamine layer. Both AMP-Ti were bactericidal against MRSA, eradicating bacteria upon contact for 6 h in a culture medium supplemented with human plasma proteins. The AMP-Ti immunomodulatory potential was evaluated using human primary macrophages, by assessing surfaces capacity to induce pro-/anti-inflammatory (M1/M2) markers and cytokines. While in naïve conditions both AMP-Ti surfaces slightly promoted the M2 marker CD163, in response to LPS and IFN-γ (simulating a bacterial infection), both AMP increased the M1 marker CCR7 and enhanced macrophage secretion of pro-inflammatory IL-6 and TNF-α cytokines, particularly for Ti-MSI78 surfaces. Additionally, both AMP-Ti surfaces were cytocompatible and promoted osteoblastic cell differentiation. This proof-of-concept study demonstrated the high potential of Dhvar5- and MSI78-Ti as antimicrobial coatings for ODRI prevention. Statement of significance: This study investigates the bactericidal effects of the antimicrobial peptides Dhvar5 and MSI78, immobilized on titanium (Ti) surfaces through a polydopamine coating, aiming at the prevention of Orthopedic-Device Related Infections (ODRIs). The developed coatings displayed MRSA-sterilizing activity, while revealing an immunomodulatory potential towards macrophages and promoting osteoblastic cell differentiation. This strategy allows a quick and easy immobilization of high quantities of AMP, unlike most other approaches, thus favoring its clinical translation.
Keywords: Antibacterial activity; Antimicrobial peptides; Dopamine; Immunomodulation; Macrophages; Surface immobilization